The Quality assessment of primary schools - Pečar, Zdravko (Organizacija (Kranj), 2007)
This paper explores themes from the management of the public sector, which is increasingly connected to the models and thinking of the private sector. This is also for primary schools. The results of quality assessment in primary schools from six European countires are represented in this paper. They show that quite substantial differences exist between countries in most quality elements, and that the final level of quality assessed depends not only on the resulting elements` grades but also on their importance/weight. We find out that Slovenian grades are pretty good, but there are still areas - e.g.educational programs - that have to be improved in the future.
Keywords: management; osnovne šole; vodenje; upravljanje; kvaliteta; zagotavljanje kvalitete